2016
DOI: 10.19082/2977
|View full text |Cite
|
Sign up to set email alerts
|

Does Hypothyroidism Affect Post-Operative Outcome of Patients Undergoing Carpal Tunnel Release?

Abstract: IntroductionRisk factors associated with Carpal Tunnel Syndrome include repetitive use of hand and wrist, advanced age, obesity, pregnancy, diabetes mellitus and thyroid disease. Decompression of the median nerve is the last treatment of choice usually indicated when negative results to conservative treatments remain for three months. In this study, we aimed to find out whether hypothyroid patients would respond to CTS surgical decompression differently in comparison to healthy individuals.MethodsThis case con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In terms of CTS risk factors, our results demonstrate the significant association between BMI and hyperthyroidism (p-value = .001) and explain the relationship of other sociodemographic factors, such as gender, which associate with hypothyroidism, but this relation is not statistically significant. However, gender significantly predicts hypothyroidism as reported by Roshanzamir, Mortazavi, and Dabbaghmanesh (2016) [ 20 ].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In terms of CTS risk factors, our results demonstrate the significant association between BMI and hyperthyroidism (p-value = .001) and explain the relationship of other sociodemographic factors, such as gender, which associate with hypothyroidism, but this relation is not statistically significant. However, gender significantly predicts hypothyroidism as reported by Roshanzamir, Mortazavi, and Dabbaghmanesh (2016) [ 20 ].…”
Section: Discussionmentioning
confidence: 65%
“…CTS could be predicted with many risk factors, such as age, obesity, pregnancy, excessive hand and wrist usage, along with hypothyroidism [ 20 ]. In terms of CTS risk factors, our results demonstrate the significant association between BMI and hyperthyroidism (p-value = .001) and explain the relationship of other sociodemographic factors, such as gender, which associate with hypothyroidism, but this relation is not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients with diabetes mellitus and thyroid disorders were excluded from the study population [ 1 ]. Various studies have demonstrated that both conditions have a negative impact on post-CTR outcomes [ 7 , 8 ]. This raises the question that if these patients were included in the trial, this may have led to different results.…”
mentioning
confidence: 99%